Neoadjuvant chemotherapy and fertility preservation in breast cancer treatment - Hosseinzadeh, Sara; Adwani, Asha (Journal of the Nuffield Department of Surgical Sciences, 2022)
Breast cancer accounts for the majority of cancers in women worldwide, and the most common cancer overall in the UK. It is typically treated by a combination of surgical and medical therapies, which commonly include neoadjuvant and/or adjuvant chemotherapy. Neoadjuvant chemotherapy in favour of adjuvant chemotherapy alongside surgery in the treatment of breast cancer confers no overall and disease-free survival advantage. Nonetheless, neoadjuvant chemotherapy is commonly favoured as a first line therapy for breast cancer. The case reported illustrates the potential for fertility considerations to delay treatment where neoadjuvant chemotherapy is the first line treatment for an operable, non-metastatic breast cancer. Here, the time taken for the patient to reach a decision on fertility preservation resulted in significant delays to treatment which, had surgery been chosen as the first line treatment, would have been prevented. This report discusses the evidence for neoadjuvant chemotherapy in favour of adjuvant chemotherapy alongside surgery in breast cancer treatment, and concludes that due to the comparable overall and disease-free survival rate, as well as the continuing upward trend in the average age of primigravida in the UK, fertility considerations present a strong argument in favour of surgery as first line therapy for non-metastatic, operable breast cancer, in favour of neoadjuvant chemotherapy.